2008
DOI: 10.1029/2007jd009744
|View full text |Cite
|
Sign up to set email alerts
|

Optical constants of ice from the ultraviolet to the microwave: A revised compilation

Abstract: [1] A compilation of the spectral absorption coefficient of ice Ih is presented for temperatures near the melting point, superseding the compilation of Warren (1984). Significant changes are made to nearly all spectral regions. The blue and near-ultraviolet absorption is much weaker than the prior estimates, which were already very small. The near-infrared absorption coefficient differs by as much as a factor of 2 from the prior compilation at some wavelengths. The midinfrared absorption coefficient is rather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
976
7
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,028 publications
(1,003 citation statements)
references
References 44 publications
19
976
7
1
Order By: Relevance
“…At 1550 nm, the optical constant used was n 1550 =1.2907+i4.586×10 −4 . The real part is that of Warren and Brandt (2008). For the imaginary part, Gosse et al (1995) recommend 4.26×10 −4 at −22 • C, with an error of 3% and a temperature dependence of 0.6% K −1 (Warren and Brandt, 2008), so that our value is within the acceptable range.…”
Section: Reflectance Modeling At 1310 Nmmentioning
confidence: 84%
See 2 more Smart Citations
“…At 1550 nm, the optical constant used was n 1550 =1.2907+i4.586×10 −4 . The real part is that of Warren and Brandt (2008). For the imaginary part, Gosse et al (1995) recommend 4.26×10 −4 at −22 • C, with an error of 3% and a temperature dependence of 0.6% K −1 (Warren and Brandt, 2008), so that our value is within the acceptable range.…”
Section: Reflectance Modeling At 1310 Nmmentioning
confidence: 84%
“…In all cases we used a log-normal distribution with σ =1.6, as observed in Antarctica by Grenfell and Warren (1999), and which resolves all sizes between 0.2 and 5 r eff , where r eff =3/(ρ ice SSA) is the effective radius. At 1310 nm, the ice optical constant used was n 1310 =1.29584+i1.302×10 −5 , based on the compilation of Warren and Brandt (2008). The real part used is that of the compilation.…”
Section: Reflectance Modeling At 1310 Nmmentioning
confidence: 99%
See 1 more Smart Citation
“…2. The small imaginary component of the ice refractive index at millimetre-wavelengths (Warren and Brandt, 2008) makes scattering the key mechanism for attenuation, even at small masses (compare the yellow and cyan lines in Fig. 3).…”
Section: Hydrometeor Attenuationmentioning
confidence: 99%
“…The optical properties, extinction coefficient (β e ) and single-scattering albedo depend on complex refractive index, particle size, particle shape and wave number. The real and imaginary parts of the complex refractive indices of ice (Warren and Brandt, 2008), volcanic ash (Volz, 1973), volcanic ash components (andesite, basalt, basaltic glass, and obsidian Pollack et al, 1973) and sulfate aerosol (Hummel et al, 1988) are shown in Fig. 1a and b for MIPAS band A.…”
Section: From Optical Properties To Infrared Limb Spectramentioning
confidence: 99%